Integrating Mobile Robots into Automated Laboratory Processes: A Suitable Workflow Management System. (April 2021) - Thurow, Kerstin; Gu, Xiangyu; Göde, Bernd; Roddelkopf, Thomas; Fleischer, Heidi; Stoll, Norbert; Neubert, Sebastian
The general trend of automation is currently increasing in life science laboratories. The samples to be examined show a high diversity in their structures and composition as well as the determination methods. Complex automation lines such as those used in classic industrial automation are not a suitable solution with respect to the required flexibility of the systems due to changing application requirements. Rather, full automation requires the connection of several different subsystems, including manual process steps by the laboratory staff. This requires suitable workflow management systems that enable the planning and execution of complex process steps. The integration of mobile robots for transportation tasks is currently an important development trend for realizing full automation in life science laboratories. The article "Workflow Management System for the Integration of Mobile Robots in Future Labs of Life Sciences" presents the development and application of a hierarchical workflow management system (HWMS) as a top-level process management and control system. This concept combines the typical hierarchical automation structure with novel approaches for the integration of transportation tasks with variable degrees of automation. The aim is to create a general-purpose workflow management system that can be used in different areas of the life sciences, regardless of the specific device components and applications used.